The Legal Landscape of Concussion: Implications for Sports Medicine Providers. (September 2016) - Albano, Andrew W.; Senter, Carlin; Adler, Richard H.; Herring, Stanley A.; Asif, Irfan M.
Context: Concussion legislation has been enacted in all 50 of the United States, aiming to prevent mild traumatic brain injuries and the potential long-term sequelae of these injuries in youth athletics. Sports medicine providers, in addressing this major public health concern, are tasked with adhering to the established standards of medical care while also considering the legal implications. Evidence Acquisition: The PubMed (2011-2016) database was searched using the following search terms: concussion, sports concussion, legislation, and concussion legislation . References from consensus statements, review articles, and book chapters were also utilized. Study Design: Clinical review. Level of Evidence: Level 4. Results: The Lystedt law and its progeny have increased awareness of the signs and symptoms of sports concussion, but adherence to state legislation can pose some challenges. Conclusion: The presence of concussion legislation places a responsibility on the sports medicine provider to have a firm understanding of the legality of concussion management in the state(s) in which they practice.